An Impact of Tools of Promotion and Situational Factors’ on Consumer Buying Behaviour: Understanding the Impact of Promotional Tools and Situational Factors on Indian Consumer Buying Behavior (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Companies expend huge amounts of funds as budgets for sales promotion oriented activities. The objective is to promote the produces more attractively and valuably. The goal is to offer the merchandise more attractive and valuable in the eyes of the consumers. A free of cost sample, giving a discount, physical, social environment personated an important part in the advancement of purchasing behavior of consumer and sales promotion. As per the new need of the present era as the knowledge regarding the association between promotional tools and consumers helps in framing the marketing strategies to attract potential customers and converting them active customers which would lead to higher sales promotions are very important these days to motivate Indian buying pattern.